A Phase 3, double-blind, placebo-controlled efficacy and safety study of ADS-5102 (Amantadine) extended-release capsules in people with multiple sclerosis and walking impairment. (April 2022) - Cohen, Jeffrey A; Cameron, Michelle H; Goldman, Myla D; Goodman, Andrew D; Miller, Aaron E; Rollins, Anne; Llorens, Lily; Patni, Rajiv; Elfont, Robert; Johnson, Reed
Background: ADS-5102, a delayed-release, extended-release (DR/ER) amantadine, improved walking speed in MS in a Phase 2 trial. Objective: The aim of this study was to present primary results of a Phase 3, double-blind, ADS-5102 trial (INROADS) for walking speed. Methods: Adult participants with MS and walking impairment, not currently using amantadine or dalfampridine, underwent 4-week placebo run-in before randomization 1:1:1 to placebo, 137 or 274 mg/day ADS-5102 for 12 weeks. Primary outcome was the proportion of responders (20% increase in Timed 25-Foot Walk (T25FW) speed) for 274 mg ADS-5102 versus placebo at end of double-blind (Study Week 16). Additional measures included Timed Up and Go (TUG), 2-Minute Walk Test (2MWT), and 12-item Multiple Sclerosis Walking Scale (MSWS-12). Results: In total, 558 participants were randomized and received double-blind treatment. Significantly more participants responded with 274 mg ADS-5102 (21.1%) versus placebo (11.3%). Mean T25FW speed also significantly improved (0.19 ft/s) versus placebo (0.07 ft/s). Other measures were not significant using prespecified hierarchical testing procedure. Adverse events led to discontinuation for 3.8% (placebo), 6.4% (137 mg ADS-5102), and 20.5% (274 mg ADS-5102). Conclusion: INROADS met its primary endpoint, showing a significantly greater proportion of participants with meaningful improvement in walking speed for 274 mg ADS-5102 versus placebo. Numeric dose response was seen for some secondary efficacy outcomes and adverse events.